2021
DOI: 10.3390/ma14206064
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design Method for Constructions: Simulation, Manufacturing and Experiment

Abstract: The development of additive manufacturing technology leads to new concepts for design implants and prostheses. The necessity of such approaches is fueled by patient-oriented medicine. Such a concept involves a new way of understanding material and includes complex structural geometry, lattice constructions, and metamaterials. This leads to new design concepts. In the article, the structural design method is presented. The general approach is based on the separation of the micro- and macro-mechanical parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 34 publications
(46 reference statements)
0
20
0
Order By: Relevance
“…In addition, the RVE approach allows easier control of the structure of the object under study. In the previous study, 69 only a structural design algorithm was applied. In contrast to this study, structural changes were made only in the longitudinal direction of the considered body.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the RVE approach allows easier control of the structure of the object under study. In the previous study, 69 only a structural design algorithm was applied. In contrast to this study, structural changes were made only in the longitudinal direction of the considered body.…”
Section: Discussionmentioning
confidence: 99%
“…Let's consider a body with volume V in space R 3 with boundary V. The mechanical behavior of a long‐bone endoprosthesis can be described with the linear theory of elasticity by the following equations 69 : σtrue~=0,xtrue→V0, εtrue~=12utrue→+()trueuT,xtrue→V0, σtrue~=trueC~true~:εtrue~,xtrue→V0, utrue→=0,xtrue→Sitalickin, σtrue~ntrue→=ptrue→,xtrue→Sitalicsta, SitalicstaSitalickin=V, VitalicconV0, where V ° = V ∩∂ V , V con is the constant region, u is the displacement vector, …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, in numerical calculations, it was shown that stress distribution does not depend on stiffness properties [ 18 ]. This can be explained by using a linear model in simulation.…”
Section: Methodsmentioning
confidence: 99%